Co-fermentation of Lactiplantibacillus plantarum and Saccharomyces cerevisiae enhances the flavor characteristic of mature coconut water: Insights from volatile and non-volatile profiles - Wen Xu; Qianqian Li; Zeming Song; Xiaoping Hu; Kun Cai; Lin Zhang; Xue Lin; Sixin Liu; Congfa Li; Qingyang Xu (Food Chemistry: X, 2025)
The mature coconut water (MCW) is rich in nutrients, but its sour and astringent taste makes it unsuitable for direct consumption. In this study, a co-fermentation system employing Saccharomyces cerevisiae and Lactiplantibacillus plantarum was developed to enhance the flavor of MCW, wherein an indigenous S. cerevisiae 1–7-1 was screened for optimal sensory characteristics when co-fermented with L. plantarum A33. Co-fermentation changed odor and taste characteristics of MCW with a broad range of organic compounds and the high richness taste attribute. Compared to fermentation with L. plantarum A33, co-fermentation increased total volatiles content from 81,487 μg/L to 996,944 μg/L, with characteristic aroma-active compounds identified as ethyl caprylate (91,032 μg/L), ethyl caprate (35,160 μg/L), isoamyl alcohol (136,376 μg/L), octanoic acid (267,673 μg/L), and isoamyl acetate (25,336 μg/L). The amino acid metabolic pathway was the most significantly perturbed pathway during co-fermentation. This study provides an innovative strategy for developing value-added MCW-based beverages.